MOTIVASI INDONESIA MELAKUKAN KERJASAMA DI BIDANG INDUSTRI KIMIA DENGAN SENEGAL TAHUN 2013-2016 - Nur Maida; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Senegal is one of the countries located in West African that included into Sub-sahara African. This state well known has a source of mining potential specially phosphate and uranium that can increase national and regional incomes. Many country which are represented by many multinational corporations are investing in Senegal,especially in industrial sectors. And in this research, writer focused on the chemical industrial sector cooperation by Indonesia and Senegal.The reasearch is qualitative with descriptive analysis method. In analyzing the motivation of Indonesia cooperates with senegal in chemical industrial sector 2013-2016. The writer uses a Neoliberal perspective the supported by the concept of International cooperation. The theory used is Mercantilist theory.The results of this study that motivation of Indonesia cooperates with Senegal influenced by several factors there are, economic policy of Senegal, natural resource specially in industry and mining sector of Senegal, and also this cooperation aimed to the implementation of New Asian-African Strrategic Parnership (NAASP), was founded in 2005 by asian african countries for the future cooperation between two continents that is the joint strategic the country from Asian and African.Keywords : International Cooperation, Economic Policy, NAASP, Phosphate mining Sector, Senegal, West Africa